2018
DOI: 10.26911/thejhpm.2018.03.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Completeness of Inpatient Medical Record Filling in Dr. R Sosodoro Djatikoesoemo, Bojonegoro, East Java

Abstract: Background: Medical records are central to all patient healthcare activities. Fundamentally, they form part of a doctor's ethical and statutory duty in providing good patient care.Good quality medical records, including completeness of record filling, are essential to proper ongoing care of the patient and are paramount for effective communication between healthcare professionals and their patients. However, studies in Indonesia examining factors associated with the completeness of inpatient medical record fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
2
0
3
Order By: Relevance
“…Our study revealed that supportive supervision by higher-level officials is another significant factor linked to the good completeness of data in institutional birth. This finding is consistent with prior studies conducted in Ethiopia and Indonesia [ 65 , 66 ], which highlighted the effectiveness of supportive supervision in improving health care data quality. Therefore, Policymakers, program managers, and officials at the district and higher administrative levels need to prioritize strengthening regular supervision and directives for healthcare facilities, enabling healthcare providers to promptly identify and correct data quality gaps in the services they deliver [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that supportive supervision by higher-level officials is another significant factor linked to the good completeness of data in institutional birth. This finding is consistent with prior studies conducted in Ethiopia and Indonesia [ 65 , 66 ], which highlighted the effectiveness of supportive supervision in improving health care data quality. Therefore, Policymakers, program managers, and officials at the district and higher administrative levels need to prioritize strengthening regular supervision and directives for healthcare facilities, enabling healthcare providers to promptly identify and correct data quality gaps in the services they deliver [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…Selain itu, berbagai upaya edukasi kesehatan yang diberikan pada pasien tuberkulosis juga telah diberikan namun tindakan pencegahan penularan tuberkulosis masih belum optimal. Penanganan tuberkulosis sangat diperlukan agar pasien tuberkulosis yang terdiagnosis dapat berkomitmen dalam pengobatan sampai dengan selesai (Pratama et al, 2018).…”
Section: Pendahuluanunclassified
“…Di amerika menunjukkan 71 % sudah mampu melakukan dokumentasi keperawatan menggunakan teknologi informasi dan 71,98% perawat setuju dan sudah memahami menggunakan dokumentasi berbasis elektronik untuk meningkatkan pengetahuan dan kemampuan tentang dokumentasi keperawatan (Chand & Sarin, 2019;McNicol, et al, 2018). Di Indonesia, dokumentasi keperawatan mencapai 71,2% dan 73,2% yang dilaksanakan masing-masing di rumah sakit dan di tingkat pelayanan primer (Pratama et al, 2018;. Proses pelaksanaan dokumentasi berbasis elektronik tentunya harus sesuai dengan standar dokumentasi keperawatan dan terminology dalam pelaksanaan dokumentasi keperawatan.…”
Section: Pendahuluanunclassified